Investment and the Cross‐Section of Equity Returns - CLEMENTI, GIAN LUCA; PALAZZO, BERARDINO (Journal of Finance, 2019)
ABSTRACT The data show that, upon being hit by adverse profitability shocks, large public firms have ample latitude to divest their least productive assets, reducing the risk faced by shareholders and the returns that they are likely to demand. In the one‐factor production‐based asset pricing model, when the frictions to capital adjustment are shaped to respect the evidence on investment, the model‐generated cross‐sectional dispersion of returns is only a small fraction of that documented in the data. Our conclusions hold even when operating or labor leverage is modeled in ways shown to be promising in the extant literature.